Investigation of the structural, electronic, optical, elastic, and thermodynamic properties of the zinc blende Ga1-xAlxAs1-yPy quaternary alloys: A DFT-Based simulation. (May 2021) - Moussa, R.; Abdiche, A.; Khenata, R.; Ahmed, R.; Tahir, S.A.; Omran, S. Bin; Bouhemadou, A.
Abstract: In this work, the effect of the composition on the structural, electronic, elastic, optical and thermodynamic properties of the Ga1-x Alx As1-y Py quaternary alloys are investigated using the full-potential augmented plane wave plus local orbitals (FP-APW + lo) approach in the density functional theory framework as embodied in the WIEN2k computational package. The fundamental physical properties of the cubic Ga1-x Alx As1-y Py quaternary alloys, such as lattice constant, bulk modulus, energy band structure and elastic constants, are predicted for the first time. The obtained results show that the Ga1-x Alx As1-y Py quaternary alloys are direct band gap semiconductors, while their parents; GaP, AlAs, and AlP binary compounds are indirect band gap semiconductors. It is found that the studied materials are of brittle character and ionic bonding nature. The static dielectric constant and static refractive index of the considered alloys are calculated and compared with the obtained results using empirical models. Pressure and temperature dependencies of some thermodynamic parameters of the title quaternary alloys are also investigated and discussed. Highlights: Fundamental physical properties of the Ga1-x Asx Al1-y Py quaternary alloys are determined. The structural, properties of Ga1-x Asx Al1-y Py  alloys show the possibility of the deposition on GaAs and AlAs substrates. The Ga1-x Asx Al1-y Py quaternary alloys are wide band gap semiconductors and they are brittle in nature. . The thermodynamic parameters dependences on (P, T) of the Ga1-x Asx Al1-y Py  for x=y=0.5 and x=y=0.25 are calculated. The CV  and the entropy S of the alloys are strongly affected when changing temperature at constant pressure.